Ethics: Essential works of Foucault 1954-1984: Volume 1 - Foucault, Michel 1926-1984; Rabinow, Paul (London Penguin Books, 1994)
This is the first of three volumes collecting the most significant writings and interviews of Michel Foucault outside his published monographs. "Ethics" contains Foucault's summaries of the highly influential courses he taught at the College de Francefrom 1970 to 1982 (hitherto never translated into English), as well as engaging and unusally candid interviews and Foucault's key writings on ethics. 'A fabulous journey through thirty years of political and intellectual ferment that shows that Foucault's work is as alive and contemporary as ever' - Didier Eribon.